'Maths on the move': Effectiveness of physically-active lessons for learning maths and increasing physical activity in primary school students. Issue 8 (August 2020) - Vetter, M.; O'Connor, H.T.; O'Dwyer, N.; Chau, J.; Orr, R.
Abstract: Objectives: This study evaluated the benefit of physically-active lessons for learning maths multiplication-tables. The impact of the intervention on general numeracy, physical activity (PA), aerobic fitness, body mass index (BMI) and school-day moderate to vigorous PA (MVPA) was also assessed. Design: Randomised controlled cross-over trial. Method: Year 3 students (n = 172, mean age 8.4 ± 0.3 years, 48% male) were recruited from 10 classes across two urban primary schools. Participants were randomly assigned to a seated classroom (Classroom) group or physically-active lessons in the playground (Playground) and crossed over to the alternative condition in the subsequent school term. The 6-week intervention comprised 3 × 30 min sessions/week. Multiplication-tables (teacher-designed test) and general maths (standardised test) were assessed pre- and post-intervention. Aerobic fitness was assessed via the shuttle-run. Pre- to post-intervention change scores were compared for analysis and effect sizes (ES) calculated. Total PA and MVPA were assessed with accelerometers in a subset of participants. Results: Multiplication scores improved significantly more in Playground than Classroom groups (ES = 0.23; p = 0.045), while no significant differences were observed in general numeracy (ES = 0.05; p = 0.66). Total PA and MVPA were substantially higher during Playground than Classroom lessons (ES: total PA = 7.4, MVPA = 6.5; p < 0.001) but there were no differences in PA/MVPA between the groups throughout the rest of the school day. Aerobic fitness improved more in Playground than Classroom groups (ES = 0.3; p < 0.001) while the change in BMI was not different between groups (p = 0.39). Conclusions: Physically-active lessons may benefit the learning of maths multiplication-tables while favourably contributing to school-day PA/MVPA.